2017
DOI: 10.22454/primer.2017.703541
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effects of a Health Literacy Curriculum for Family Medicine Residents

Abstract: Introduction: Improving education about health literacy for health care professionals has been recommended, and many US family medicine residency programs have developed such curricula. Few studies have evaluated the effectiveness of health literacy curricula for health care professionals. This pilot study aimed to determine whether a longitudinal health literacy curriculum for family medicine residents could achieve long-term sustained improvements in health literacy knowledge and clear communication practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 20 publications
2
37
0
1
Order By: Relevance
“…In conclusion, this study provides a baseline assessment of diabetes educator communication practice. Our findings suggest that health literacy and communication in health professional school curricula positively affects diabetes educators' communication practices, supporting efforts to develop standards for health literacy curricula and competencies (Coleman, Peterson-Perry, & Bumsted, 2016). In this study, Hispanic educators reported using more communication techniques than their Caucasian counterparts; future research examining the use of communication techniques by racial and ethnic minority health professionals are needed to further explore these findings.…”
Section: Resultssupporting
confidence: 61%
“…In conclusion, this study provides a baseline assessment of diabetes educator communication practice. Our findings suggest that health literacy and communication in health professional school curricula positively affects diabetes educators' communication practices, supporting efforts to develop standards for health literacy curricula and competencies (Coleman, Peterson-Perry, & Bumsted, 2016). In this study, Hispanic educators reported using more communication techniques than their Caucasian counterparts; future research examining the use of communication techniques by racial and ethnic minority health professionals are needed to further explore these findings.…”
Section: Resultssupporting
confidence: 61%
“…Health professions educators and others should match selected health literacy practices with their own underlying competencies when designing learning activities. (Coleman, et al, 2013) It should be noted, however, that although a variety of educational studies have reported positive effects of health literacy and clear communication curricula on knowledge and skills for health professionals (Coleman, Peterson-Perry, & Bumsted, 2016b; Coleman & Fromer, 2015; Toronto & Weatherford, 2015; Green, Gonzaga, Cohen, & Spagnoletti, 2014; Mackert, Ball, & Lopez, 2011; Coleman, 2011), to our knowledge, no studies have reported an effect of such interventions on patient-centered outcomes. Furthermore, in the absence of information regarding the cost of implementing training interventions to achieve health literacy and clear communication practices, it is not possible to comment on the actual resources needed for such interventions.…”
Section: Discussionmentioning
confidence: 77%
“…A disease-management intervention that incorporates plain language, teach-back, and visual aids is associated with a greater likelihood of achieving prescribed health outcomes [44]. Previous research had indicated that health literacy interventions for medical students—including teaching plain language skills, teach-back techniques, and the use of universal precautions—lead to significant improvement in self-reported knowledge and planned behaviors [45]. Medical educators can assist residents and clinicians with using these strategies and developing these skills to effectively communicate health information to patients and caregivers.…”
Section: Discussionmentioning
confidence: 99%